Economic Interests of Media in the Coverage of the News Value of Sex on the Harian Rakyat Aceh - Hamdani M. Syam; Nur Anisah; Rahmat Saleh; Abdul Rani Usman; Dini Khairani (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2020)
In addition to having the freedom to spread news to the public, the press also have the freedom to search and process news. In exercising that freedom, journalists always consider that news must be interesting so that people want to read it. The media coverage of sex, including stories on rape, sexual harassment, adultery, cheating, and sordid topics, is a news value that has a high rating for people. Sometimes in the economic interests of the media, journalists violate the norms and ethics of the news. This study is aimed to examine through content analysis the coverage of sex in the Harian Rakyat Aceh newspaper, which from January to April 26 featured 54 articles related to sex. This study examined this coverage in the context of Indonesia’s implementation of the journalistic code of ethics. Indonesian journalists are prohibited from mixing facts and opinions and from reporting sadistic and obscene news. Using the Holsti formula, inter-coder reliability resulted in a CR of 0.99, showing strong reliability. After data collection, coding sheets were analyzed using SPSS software to determine the results of each category. This study found that the news value of the 54 articles in the Harian Rakyat Aceh newspaper is considered to have violated the journalistic code of ethics. Thus, it can be assumed that there is an economic interest in the media’s reporting of sex in that newspaper.